The Impact of a Quality Assurance System and Leadership on the Performance of Lecturers at Banten Private Universities - Subai; Syadeli Hanafi; Sholeh Hidayat (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
Public participation, research and publication, and teaching are all associated with higher educational standards. University administrators must be competent and dedicated if they want to see improved performance. This study aims to investigate how Banten Private Universities' degree programs are affected by peer pressure and the quality system. The multiple line regression approach was employed in this investigation. There were 48 dosages among the research subjects. Angles were used to gather data. The influence on lecturer performance is considerable, according to the linearity test results, which have a significance level of Sig. 0.010 <0.05. As a result, it is evident that H1 is accepted and Ho is rejected, demonstrating the strong and favorable effects of behavioral system and leadership characteristics on lecturer.